Seguridad alimentaria en tiempos de Covid – 19. Un estudio a la disponibilidad, acceso y consumo en los hogares de la Ciudad de Riobamba. - Martínez Lliguin, Gisel Cristina (2022)
The covid – 19 triggered an emergency to food safety causing a crisis in availability, access and population consumption a sufficient and nutritious food supply. This study will establish the most important factors that determine food safety in the health crisis caused by covid – 19; for this study problem the descriptive – correlational methodology will be used, which demonstrated the main the household’s characteristics in Riobamba city and variables behavior in covid – 19 contexts, supported by deductive method. The main study finding is the predominant factor that affected food security compliance in Riobamba city during the health crisis, this was food access, which involves important aspects such as infrastructure and roads, family incomes, basic food basket price, food and nutrition education that were affected in confinement. Together the lack involvement government sector through regulations and citizens education in relation to food safety and interest lack of private sector offering healthy and quality food.